Characteristic brain magnetic resonance imaging pattern in patients with macrocephaly and PTEN mutations. Issue 3 (20th December 2013) - Vanderver, Adeline; Tonduti, Davide; Kahn, Ilana; Schmidt, Johanna; Medne, Livija; Vento, Jodie; Chapman, Kimberly A.; Lanpher, Brendan; Pearl, Phillip; Gropman, Andrea; Lourenco, Charles; Bamforth, John‐Steven; et al.
Abstract We describe an MRI phenotype seen in a series of patients with mutations in PTEN who have clinical features consistent with PTEN hamartoma tumor syndrome (PHTS). Retrospective review of clinical data and MRI was performed in 23 subjects evaluated in four different tertiary care centers with clinical programs in inherited disorders of the white matter. Patients were referred due to abnormal MRI features and abnormal PTEN sequencing was identified. All subjects had significant macrocephaly (on average >4 SD above the mean), developmental delay with or without autism spectrum disorder and uniform MRI features of enlarged perivascular spaces and multifocal periventricular white matter abnormalities. The phenotype of PHTS may include MRI abnormalities such as multifocal periventricular white matter abnormalities and enlarged perivascular spaces. These neuroimaging findings, in association with macrocephaly and developmental delay, should prompt consideration of PTEN as a diagnostic possibility. © 2013 Wiley Periodicals, Inc.